An Analysis of ECB Monetary Policy and Stock Price Movements - Pishinov, Petko (Research Papers, 2024)
A number of economists and researchers have mentioned that apart from inflation and output gap (GDP gap), asset price movements are also important in refining monetary policy of a Central bank and should be considered as equal as the two other determinants. Thus, this research aims to investigate the monetary policy of ECB during the financial crisis period by examining the suitability of the interest rate setting based on inflation, output gap, and stock price movement.